2020
DOI: 10.1111/ffe.13205
|View full text |Cite
|
Sign up to set email alerts
|

Residual fatigue life prediction based on a novel damage accumulation model considering loading history

Abstract: The influence of prior low‐cycle fatigue (LCF) on the residual fatigue life was investigated experimentally. A Ni‐based alloy was cyclically loaded under stress‐controlled low‐high (LH) block loading. In the first loading step, low‐amplitude loading was performed with the stress amplitude of 283.5MPa at 710°C. Different cycles of preloading were performed, varying from 100 to 10 000. Subsequently, high‐amplitude fatigue loading was carried out with the stress amplitude of 315MPa at 800°C. Experimental results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 81 publications
0
34
0
Order By: Relevance
“…More recently, Taheri et al 12 and Belattar et al 13 reported that the effect of pre-hardening on the fatigue life of 304 L stainless steel was detrimental in strain control and beneficial in stress control. In our previous study, 14 the authors found that the cyclic loading history (with low amplitude at 710 C) was beneficial to the subsequent fatigue life (with high amplitude at 800 C) of K417 alloy when the previously consumed life fraction is below 0.2. The nickel-based alloy also exhibited initial cyclic hardening under the in-phase thermal-mechanical fatigue (TMF) loading.…”
Section: Introductionmentioning
confidence: 90%
“…More recently, Taheri et al 12 and Belattar et al 13 reported that the effect of pre-hardening on the fatigue life of 304 L stainless steel was detrimental in strain control and beneficial in stress control. In our previous study, 14 the authors found that the cyclic loading history (with low amplitude at 710 C) was beneficial to the subsequent fatigue life (with high amplitude at 800 C) of K417 alloy when the previously consumed life fraction is below 0.2. The nickel-based alloy also exhibited initial cyclic hardening under the in-phase thermal-mechanical fatigue (TMF) loading.…”
Section: Introductionmentioning
confidence: 90%
“…Similarly, Li et al 29 have proposed a nonlinear model in order to account for the influence of the previously consumed life as…”
Section: Two-step or Variable Amplitude Loadingmentioning
confidence: 99%
“…Cumulative damage models by introducing a fatigue driving stress concept such as that by Kwofie and Rahbar 27 and the S-N curve approach by Zuo et al 28 are also found to be effective to account for the load history effect. A damage concept based on cycle-by-cycle analysis of S-N curve was presented by Mesmacque et al 20 Recently, Li et al 29 have briefly reviewed many of the available nonlinear damage model and studied the effect of low-cycle fatigue loading on the residual fatigue life of a Ni-based alloy cyclically loaded under stress-controlled low-high block loading.…”
Section: Introductionmentioning
confidence: 99%
“…Under different load sequences, the sudden changes in load amplitude will lead to changes in the damage evolution of subsequent load cycles, thereby affecting the remaining useful life of the bearings. In addition, it is also found that the interactions of loads also have a big influence on the fatigue life of components 7–12 . However, Miner's rule fails to consider these influences, which often leads to overestimation or underestimation of fatigue life.…”
Section: Introductionmentioning
confidence: 99%